2014
DOI: 10.5751/ace-00662-090108
|View full text |Cite
|
Sign up to set email alerts
|

Crop type influences edge effects on the reproduction of songbirds in sagebrush habitat near agriculture

Abstract: ABSTRACT. Extensive fragmentation of the sagebrush shrubsteppe of western North America could be contributing to observed population declines of songbirds in sagebrush habitat. We examined whether habitat fragmentation impacts the reproduction of songbirds in sagebrush edge habitat near agriculture, and if potential impacts vary depending on the adjacent crop type. Specifically, we evaluated whether nest abundance and nest survival varied between orchard edge habitat, vineyard edge habitat, and interior habita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…For small passerines, Grendelmeier et al (2015) successfully identified predators in 84% of 57 depredated nests of the Wood Warbler Phylloscopus sibilatrix (Bechstein, 1793) in northern Switzerland. Knight et al (2014) (Pallas, 1764). These evidences, and our data suggest that camera systems based on motion sensors rarely achieve 100% efficiency in the detection of predators, as occurs, for example, with most devices with full time recording (time-lapse devices) (Sabine et al 2005, Pierce and Pobprasert 2007, Gula et al 2010, Kirkpatrick and Conway 2010, Smith et al 2012, Denmon et al 2013.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For small passerines, Grendelmeier et al (2015) successfully identified predators in 84% of 57 depredated nests of the Wood Warbler Phylloscopus sibilatrix (Bechstein, 1793) in northern Switzerland. Knight et al (2014) (Pallas, 1764). These evidences, and our data suggest that camera systems based on motion sensors rarely achieve 100% efficiency in the detection of predators, as occurs, for example, with most devices with full time recording (time-lapse devices) (Sabine et al 2005, Pierce and Pobprasert 2007, Gula et al 2010, Kirkpatrick and Conway 2010, Smith et al 2012, Denmon et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Although the statistical significance of predator detection was not affected, we also recommend the use of two cameras per nest, because the predators were identified by only one of the cameras in many nests. In previous studies that used camera traps for a similar purpose, all were conducted in temperate habitats (Knight et al 2014, Thiebot et al 2014, Davies et al 2015, Grendelmeier et al 2015, but, based on the results of this study, camera traps are also appropriate to monitor nest predation in tropical rainforest environments.…”
Section: Brocrado Et Al 2012mentioning
confidence: 99%
See 2 more Smart Citations
“…Besides recognizing the impact of predators on prey populations, certain studies have attempted to distinguish the influence of landscape structure, especially the edge effect on nest predation, with varying results (Major and Kendal 1996;Andrén and Angelstam 1988;Lahti 2001;Evans 2004;Ellis-Felege et al 2012;Knight et al 2014). Andrén (1992) showed that Eurasian jays (Garrulus glandarius) and common ravens (Corvus corax) preyed within larger forest fragments and avoided smaller patches, whereas magpies (Pica pica) and Eurasian jackdaws (Corvus monedula) preferred agricultural land for nest predation.…”
Section: Introductionmentioning
confidence: 99%